Diastereo-selectivity in diels–alder cycloadditions of erythrose benzylidene-acetal 1,3-Butadienes with maleimides - Salgueiro, D. A. L. (2012)
Maleimides were combined with D-erythrose benzylidene-acetal 1,3-butadienes 1 and 2 to study the facial selectivity of the Diels-Alder cycloadditions. The selectivity was found to be from moderate to good. The reaction diastereotopicity can be reversed with the temperature. Simultaneous coordination of diene 1, having a free hydroxyl group, and maleimide 3 to a chiral bimetallic Lewis acid catalyst (LACASA-DA reaction) occurs with complete diastereo-control to give a single adduct, using an extra chiral inductor either R- or S-BINOL.